Cyberbullying Relationship with Social Anxiety and Social Withdrawal in Adolescents - Fahlevi, Restu Yogi; Yusuf, Ah; Krisnana, Ilya (Universitas Airlangga, 2020)
Introduction: The process of changing a person into adolescence is a very important process where in adolescence, the process of finding the identity of a teenager is ongoing, looking for self-identity, trying new things, and social processes such as having a group of friends who he thinks have one hobby with him. Commonly referred to as